S19 Interventions for the management of malignant pleural effusions. (12th November 2015) - Clive, AO; Jones, HE; Bhatnagar, R; Preston, NJ; Maskell, NA
Abstract : Aims: Malignant pleural effusion (MPE) is a common clinical problem and a number of treatment options are available to manage these patients. We undertook a systematic review of the literature and meta-analysis in order to ascertain the optimal management strategy for adults with symptomatic MPE. Methods: We searched CENTRAL, MEDLINE, EMBASE, CINAHL; SCI-EXPANDED and SSCI (ISI Web of Science) databases to May 2015. We included randomised controlled trials of intrapleural interventions for adults with symptomatic MPE. Two review authors independently extracted the data and assessed the studies' risk of bias. The primary outcome measure was pleurodesis failure rate. Secondary outcome measures were adverse effects and complications, patient reported control of breathlessness, quality of life, cost, mortality, duration of inpatient stay and patient acceptability. We performed network meta-analysis with random effects to analyse the primary outcome data and those secondary outcomes with enough data. If this was not possible, we reported the results by narrative synthesis. Results: Of the 1888 records identified, 62 randomised trials, including a total of 3428 patients, were eligible for inclusion. All studies were at high risk of bias for at least one domain and the majority were unblinded. Network meta-analysis evaluating the rate of pleurodesis failure suggested Talc Poudrage to be the most effective method (estimated rank 1 [95% CI 1, 4]). The estimated ranks of the other evaluated methods are shown in the Figure . The estimates were imprecise as evidenced by the wide credible intervals. Both statistical and clinical heterogeneity was high. The secondary outcomes were inconsistently reported. Network meta-analysis was only performed for pain, fever and mortality and minimal evidence was obtained suggesting differences between treatments for these outcomes. Indwelling pleural catheters were examined in two RCTs, both reporting improved breathlessness when compared to Talc Slurry pleurodesis, despite lower pleurodesis success rates. Conclusions: Based on the available evidence, Talc Poudrage may be the optimal method for obtaining a pleurodesis in MPE. However, there is minimal evidence to suggest large differences between the next most effective methods. Global experience of these agents and their adverse events must also be considered when selecting a sclerosant.